Lipids: A Key Regulatory Hub in Plant Stress Adaptation - Naguib, Deyala M.; Regmi, Kishor (Journal of Nepal Biotechnology Association, 2023)
The plants exert rapid responses to environmental stresses to adapt with the stress. Plants respond in many ways to different abiotic and biotic stresses. The first cellular component to sense stress signals is cell membrane. Cell membrane is a biological membrane, and its main constituents are Lipids that can sense conditions outside the cell. Remodeling of cellular membrane lipids is one of the critical mechanisms in the plant cells to withstand stresses. Lipids play a critical role in triggering and regulating cellular hormonal signaling cascades. There is a close correlation between ABA-dependent signaling and lipid metabolic pathways to maintain the integrity and the viability of cellular membranes. Phosphatidic acid, lysophospholipid, inositol phosphate, fatty acid, oxylipins, diacylglycerol, and sphingolipid are considered as the signaling molecules. Lipids also act as a stress reliever to lower the negative effects of stress. This review highlights the key regulatory roles of lipids in plant adaptation against the environmental stresses.